A Analysis of Financial Distress during the Covid-19 Pandemic: Analysis of Financial Distress during the Covid-19 Pandemic - M. Ridwan Tikollah; Muhammad Azis; Fajriani Azis; Nuraisyiah Nuraisyiah (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Financial distress is a condition where the financial status of a company is in a bad state or is experiencing a crisis. Financial difficulties are closely related to the bankruptcy of the company, because the company experienced difficulties before going bankrupt. The occurrence of financial distress was caused by many companies experiencing liquidation, including during the Covid-19 pandemic. The current Covid-19 pandemic has had a significant impact on companies, one of which is the property and real estate sector. This study aims to determine the accuracy of the prediction model in predicting financial distress during the COVID-19 pandemic in Property and Real Estate companies. The data used is data on the financial statements of 48 property and real estate companies published on the IDX during 2019-2021. The results showed that from 48 companies there were 19 companies that were consistent in the distress category, three companies that were consistent in the gray area category, and 10 companies that were consistent in the non-distress category. The highest accuracy rate occurred in 2020, which was 72.92%, then the accuracy rate in 2021 was 68.75%, and the accuracy rate during the covid-19 pandemic was 66.67%.